Estimate of genetic and phenotypic parameters for the Dorper, Red Maasai and their crosses - Kiriro, P.M. (1994)
Data accumulated over 10 years (1971-1981) by the Ministry of Livestock Development and FAO/UNDP (Food and Agriculture Organization of the United Nations/United Nations Development Programme) were analysed to estimate the growth performance of Dorper and Red Maasai sheep and their crosses. The heritability, heterosis, phenotypic and genotypic correlations were determined for birth weight, average daily gain and weaning weight.The animals' genotype, year, season and type of birth, sex of lamb and its rearing affected (P<0.01) all the growth parameters. Direct and maternal heterosis made sizeable contributions to birth weight (4.50 and 4.89%), weaning weight (10.95 and 6.50%) and average daily gain (9.36 and 8.93%). The heritability estimates were 0.14 ± 0.8, 0.08 ± 0.05 and 0.10 ± 0.06 for birth weight, weaning weight and average daily gain, respectively. These low estimates indicate that selection will not be an appropriate option for improving weaning weights and average daily gains. The genetic and phenotypic correlation estimates of the growth characteristics of Dorper lambs suggest that birth weight and average daily gain could be increased by selecting for heavier lambs at weaning.